Direct and reflected self-concept show increasing similarity across adolescence: A functional neuroimaging study - Van der Cruijsen, Renske (Neuropsychologia, 2019)
In adolescence, the perceived opinions of others are important in the construction of one’s self-concept. Previous studies found involvement of medial Prefrontal Cortex (mPFC) and temporal-parietal junction (TPJ) in direct (own perspective) and reflected (perceived perspective of others) self-evaluations, but no studies to date examined differences in these processes across adolescence. In this study, 150 adolescents between 11 and 21 years old evaluated their traits from their own perspective and from the perceived perspective of peers in a fMRI session. Results showed overlapping behavioural and neural measures for direct and reflected self-evaluations, in mPFC, precuneus and right TPJ. The difference in behavioural ratings declined with age, and this pattern was mirrored by activity in the mPFC, showing a diminishing difference in activation for direct > reflected self-evaluations with increasing age. Right TPJ was engaged more strongly for reflected > direct evaluations in adolescents who were less positive about themselves, and those who showed who showed less item-by-item agreement between direct and reflected self-evaluations. Together, the results suggest that the internalization of others’ opinions in constructing a self-concept occurs on both the behavioural and neural levels across adolescence, which may aid in developing a stable self-concept.